Komparasi Static Routing Menggunakan IPv4 Dengan IPv6 Guna Meningkatkan Quality Of Service - Tommi Alfian Armawan Sandi; Rachmat Ad Purnama; Firmansyah Firmansyah; Sujiliani Heristian (LPPM Universitas Bina Sarana Informatika, 2022)
The use of technology has recently increased in line with the increase in devices connected to the internet. The IP capacity that covers the device is starting to get out of hand. Routing is needed when the local network is already complex, especially broadcast traffic is only concentrated in each subnet/network. When using IPv4 and IPv6, a routing protocol is required for data exchange or interconnection from client to client or client to server. IPv4 routing performance decreases as the size of the routing table increases, this is due to checking the MTU header on each router and hop switch. IPv6 with its routing process is much more efficient than its predecessor, and also has the ability to manage the large capacity of the route table, so in this study the authors compare IPv4 and IPv6 in terms of static routing efficiency on MikroTik routers.